Analisis dan Perbaikan Proses Bisnis Menggunakan Metode Business Process Improvement (BPI) (Studi Kasus: Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas III Sampit) - Frydo Tio Fernando; Nanang Yudi Setiawan; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Harbormasster's and Port Authority Office Class III Sampit is an agencys has the main task of carry out superfisions and laws enforcements fields of safety and security of sailing. Inside The Harbormaster's Office and Port Authority Office Class III Sampit, there is a sailing safety section that has a business process of ship arriving permit, ship moving permit, loading and unloading permit and sailing approval. When running a business process it is found that business processes are less effective and efficient such as lack of information given to the applicant related to the submission, repeated processes occur, bookkeeping and filing are still manually so that it can cause other problems. With the emergence of these problems, the need for evalluations ands improvemenst of busines proces in order to overcome thesse probllems. The method used in analyzing root causes is the Failure Mode and Effect Analysis and Five Whys Analys methods. To do the modeling used the Business Process Modeling and Notation method, and the Busines Proces Improvements methods to improved busines procesess. After that a simulations of the curent busines process (as-is) and recommendatiion (to-be) is to find out how much time is gained. In the business process simulation report the ship arrived an increase in time by 66.21%. The increase was due to an improvement in the activities and utilization of information systems in carrying out business processes recommendations.